Trade Liberalization and Tax Reform in the Southern Mediterranean Region - Abed, George (IMF Working Papers; Working Paper, 1998)
The European Union's Association Agreements with several countries in the Southern Mediterranean Region (SMR) aim to promote deeper economic integration between the SMR and the EU by establishing a free trade area in twelve years. Because a large share of the SMR countries' total imports comes from the EU, the removal of import tariffs could reduce budgetary revenue by the equivalent of 1 percent to 4 percent of individual countries' GDP. This paper proposes tax and tariff reforms that would help generate the needed compensatory revenue and, more important in the long run, reduce the distortionary effects of the tax and tariff systems and underpin higher rates of sustainable growth.